OMNIBUS LAW SEBAGAI ALTERNATIF PENYEMBUH OBESITAS REGULASI SEKTORAL - Corputty, Patrick (Faculty of Law, Universitas Pattimura, 2020)
The condition of sectoral regulation in Indonesia has been obese, the problem of obese sectoral regulation will have an impact on the death of economic growth and development. The number of overlapping sectoral regulations needs serious attention from the government, by applying the concept of the omnibus law the condition of obesity regulation can be cured, the choice of the concept of the omnibus law can be done through legal codification, both on the law and various implementing regulations at the central level, so for a the field of law can be recorded in one integrated and integrated text. With the concept of the omnibus law, which rearranges sectoral regulations that overlap in one law in a comprehensive, comprehensive and simple manner. This study tries to see from the perspective of state administration law in the framework of clarifying the conditions of obesity in sectoral regulations in Indonesia, this study uses a normative juridical method, by analyzing secondary data in the form of laws and libraries related to sectoral regulations. The results of this study indicate that the sectoral regulatory conditions in Indonesia are obese and need to be addressed by applying the concept of the omnibus law